Acceptance towards school based assessment among agricultural integrated living skills teachers: challenges in implementing a holistic assessment - Jaba, Salmiah; Hamzah, Ramlah; Bakar, Ab. Rahim; Mat Rashid, Abdullah (Universiti Tun Hussein Onn, Malaysia, 2013)
This study aims at identifying the acceptance of teachers teaching Agricultural Integrated Living Skills (ILS) towards the School Based Assessment (SBA). Acceptance is associated with teachers’ beliefs, attitudes and willingness to implement the assessment and involves a change in educational values. The quantitative approach was adapted from previous studies and contained 80 variables. The response rate was 80.5% from 322 teachers of Agricultural ILS from secondary schools throughout the country. Results showed that a majority of respondents were male teachers aged 42 years and younger and many had teaching experience in excess of 10 years. A large percentage of the respondents (86.3%) had taken a course on SBA, 60.6% were non-option teachers in agriculture, and a large percentage (51.8%) taught the subject in more than one level. The study revealed a moderate relationship between belief and practices (r = 0.391) while a weak relationship was found between attitude and teachers’ practices (r = 0.193) and between willingness and teachers’ practices (r = 0.132). Heavy workload contributed to a moderate belief that subsequently led to a weak attitude and a low willingness to implement SBA. The low level of belief, attitude and willingness clearly demonstrated that teachers’ acceptance toward holistic assessment was low. Teachers were unable to accept SBA as a shift in educational assessment methods, let alone to replace the existing system of assessment.